Nanotrap grafted anionic MOF for superior uranium extraction from seawater - More, YD; Mollick, S; Saurabh, S; Fajal, S; Tricarico, M; Dutta, S; Shirolkar, MM; Mandal, W; Tan, J-C; Ghosh, SK (Wiley, 2023)
On-demand uranium extraction from seawater (UES) can mitigate growing sustainable energy needs, while high salinity and low concentration hinder its recovery. A novel anionic metal-organic framework (iMOF-1A) is demonstrated adorned with rare Lewis basic pyrazinic sites as uranyl-specific nanotrap serving as robust ion exchange material for selective uranium extraction, rendering its intrinsic ionic characteristics to minimize leaching. Ionic adsorbents sequestrate 99.8% of the uranium in 120 mins (from 20,000 ppb to 24 ppb) and adsorb large amounts of 1336.8 mg g−1 and 625.6 mg g−1 from uranium-spiked deionized water and artificial seawater, respectively, with high distribution coefficient, KdU ≥ 0.97 × 106 mL g−1. The material offers a very high enrichment index of ≈5754 and it achieves the UES standard of 6.0 mg g−1 in 16 days, and harvests 9.42 mg g−1 in 30 days from natural seawater. Isothermal titration calorimetry (ITC) studies quantify thermodynamic parameters, previously uncharted in uranium sorption experiments. Infrared nearfield nanospectroscopy (nano-FTIR) and tip-force microscopy (TFM) enable chemical and mechanical elucidation of host-guest interaction at atomic level in sub-micron crystals revealing extant capture events throughout the crystal rather than surface solely. Comprehensive experimentally guided computational studies reveal ultrahigh-selectivity for uranium from seawater, marking mechanistic insight.